Control of Quaternary Ideal Endothermic Reactive Distillation with and without Internal Heat Integration. Issue 4 (19th February 2016) - Mathew, Anish K.; Kaistha, Nitin; Kumar, M. V. Pavan
Abstract: Decentralized control system design is evaluated for a basic and an internally heat‐integrated generic, ideal, double‐feed, two‐product reactive distillation system. The internally heat‐integrated reactive distillation column (HiRDC) is obtained via catalyst redistribution into the rectifying zone and feed tray relocation. For basic regulatory control, three two‐point control structures with a fixed reflux rate or a fixed reflux ratio operation policy are synthesized and evaluated for their closed‐loop disturbance rejection characteristics using rigorous dynamic simulations. To eliminate the purity offsets for on‐target product purities, product purity composition controllers manipulating the reflux ratio and stripping tray temperature set point are implemented. Reactive tray section composition control is necessary for on‐target product purity operation of HiRDC. Abstract : Temperature inferential control is evaluated for a basic and an internally heat‐integrated ideal quaternary endothermic reactive distillation system. Closed‐loop simulations with augmented product purity controllers for on‐spec product purity suggest the controllability of the internally heat‐integrated design to be slightly inferior.